2004
DOI: 10.1111/j.1365-2929.2004.01792.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning management systems: technology to measure the medical knowledge competency of the ACGME

Abstract: The LMS WebCT is an innovative and adaptable approach for designing a web-based course for primary care education in paediatrics. The LMS addresses the educational needs of both a clinical division and a residency programme. The LMS also provides an information technology infrastructure to measure the medical knowledge competency required by the ACGME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 20 publications
(17 reference statements)
0
19
0
Order By: Relevance
“…Studies in medical and non-medical literature have shown that students have a higher satisfaction rate with e-learning; most of these studies compared e-learning with traditional instructor-led approaches 19 20. These studies also suggest that compared with traditional methods of learning, e-learning is far more engaging due to its design, interactivity, navigation and ease of access 17 21.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in medical and non-medical literature have shown that students have a higher satisfaction rate with e-learning; most of these studies compared e-learning with traditional instructor-led approaches 19 20. These studies also suggest that compared with traditional methods of learning, e-learning is far more engaging due to its design, interactivity, navigation and ease of access 17 21.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of reports describe tools used to evaluate specific ACGME competencies. For example, a portfolio to assess practice-based learning and improvement skills over five residency programs at a community hospital (Taylor et al, 2002); a description of systems-based practice competency requirement (Doeczema et al, 2002); a bedside clinical evaluation instrument (Shayne et al, 2002); an assessment of interpersonal skills (Jouriles, 2002); an evaluation of knowledge and skills for pediatric resuscitations for emergency department residents and pediatric residents (Nadel et al, 2000), and a web-based curriculum to measure medical knowledge during an ambulatory block rotation (Johnson et al, 2004). The ACGME also supports a frequently updated website called RSVP (Recognize Success Via imPlementation) (http://www.acgme.org/ outcome/implement/rsvp.asp, 2004) that posts examples of on-going projects related to the ACGME competencies.…”
Section: Continuity Clinic Preceptorsmentioning
confidence: 99%
“…Learning-Management System (LMS) for example, is Internet-based application that facilitates deliveries of learning materials and tracking all e-learning activities for the hosting institution 24 h a day (Johnson et al, 2004). This includes simplifying and automating administrative tasks, track learners' achievement and competencies.…”
Section: Content Managementmentioning
confidence: 99%